Horrible Harry and the Dragon War - Kline, Suzy; Remkiewicz, Frank (New York : Viking, 2002)
Working on a dragon project in Room 3B leads to a war between two good friends--Harry and Song Lee.
Keywords: Friendship -- Fiction; Fighting (Psychology) -- Fiction; Schools -- Fiction; Korean Americans -- Fiction